(untitled) (Journal of Nobel Medical College, 2018)
Background: Urinary Bladder lesions are one of the most common presenting lesions in the Outpatient department. On the other hand neoplastic conditions of the urinary bladder are the major cause of morbidity and mortality. Bladder carcinoma is the 7th most common carcinoma worldwide and is the major cause of morbidity and mortality. Material & Methods: All the cystoscopic biopsy received in the Department of Pathology at Nobel medical college and teaching hospital from August 1st 2016 to July 31st 2017 was included in the study. Received cystoscopic biopsies were processed and classified as per 2004 WHO/ISUP classification of urothelial tumors Patients were also categorized according to the age and sex to find out the prevalence of urothelial lesions on them. Results: Out of the 78 patients 54 were males and 24 were females. Very few (n=15, 19.23%) cases of non neoplastic lesions were biopsied. Low grade urothelial carcinoma was the most common diagnosis in the patients which accounts for 49.2 % (n=31) of the total neoplastic conditions. Conclusion: Low grade urothelial carcinoma was the most common lesion encountered with the peak age range of 61-70 years. Journal of Nobel Medical College Volume 7, Number 1, Issue 12, January-June 2018, Page: 6-10